Transformative learning in a context of deep division: The importance of learning about self for leadership - Spooner, V.S.; John, V.M. (South African Journal of Higher Education, 2020)
Leadership training at institutions of higher learning typically foreground theories of leadership, predominantly as taught content. These programmes, however, are not premised on a context of deep division, inequality and hurt. Understanding this context is crucial for leading change in post-apartheid South Africa. The UP GIBS Nexus Leadership Programme uses an innovative and transformative pedagogy for leadership training. This represents an alternative paradigm because the programme prioritises learning about oneself and one’s beliefs over a taught curriculum. This leadership programme was specifically designed to equip leaders for the post-apartheid South African context. This article discusses findings from a qualitative study of the Nexus Leadership Programme which reveal profound learning at a personal level and an undoing of perspectives garnered from South Africa’s divided past. Data were collected from programme participants and programme managers, and reflections are explored via the lens of transformative learning theory. The themes generated from the data relate either to the nature of learning as experienced by the participants or to the need for unlearning prior meaning perspectives on race.